2017
DOI: 10.1530/jme-16-0169
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation pattern analysis of glycoprotein hormones and their receptors

Abstract: We have studied glycosylation patterns in glycoprotein hormones (GPHs) and glycoprotein hormone receptor (GPHR) extracellular domains (ECD) from different species to identify areas not glycosylated that could be involved in intermolecular or intramolecular interactions. Comparative models of the structure of the TSHR ECD in complex with TSH and in complex with TSHR autoantibodies (M22, stimulating and K1-70, blocking) were obtained based on the crystal structures of the FSH-FSHR ECD, M22-TSHR leucine-rich repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The rationale supporting the glycoform-specific activity relies on the assumption that different oligosaccharide chains may modulate the hormone-receptor structural interaction [58,60,61] and the downstream signaling cascades [57,58,62]. These considerations generated the idea that FSH variants could act as biased receptor agonists [63] and the impact of carbohydrate heterogeneity on FSH bioactivity was investigated both in vitro and in vivo [57,58].…”
Section: Fsh In Therapymentioning
confidence: 99%
“…The rationale supporting the glycoform-specific activity relies on the assumption that different oligosaccharide chains may modulate the hormone-receptor structural interaction [58,60,61] and the downstream signaling cascades [57,58,62]. These considerations generated the idea that FSH variants could act as biased receptor agonists [63] and the impact of carbohydrate heterogeneity on FSH bioactivity was investigated both in vitro and in vivo [57,58].…”
Section: Fsh In Therapymentioning
confidence: 99%
“…5). The residues, His70, His95 and Asp120, are located in an area that has been previously predicted as a possible oligomerisation site (Núñez Miguel et al 2017). However, the relative orientations of the molecules in each dimer are different.…”
Section: M22mentioning
confidence: 84%
“…In the extracellular domain of the TSHR there are six asparagines that conform to the consensus sequence for N-linked glycosylation (Asn-Xxx-Ser/Thr, where Xxx is any amino acid except proline), Asn77, Asn99, Asn113, Asn177, Asn198, Asn302 (Núñez Miguel et al 2017), and previous studies have indicated that all six glycosylation sites are glycosylated (Tanaka et al 1998). All five of the glycosylation sites that are within the TSHR260 domain have observed glycans attached in the TSHR-M22 structure ) and four of the sites (Asn77, Asn99, Asn177 and Asn198) have glycans observed in the TSHR-K1-70 structure (Sanders et al 2011).…”
Section: Crystal Structurementioning
confidence: 99%
“…Interestingly, the abundance of the glycosylated variants in FSHβ subunit appears to be physiologically regulated (141). Although glycosylations are involved in the FSH bioactivity, they are not directly interacting with the receptor binding site (11, 12, 15, 150). Removal of the carbohydrate residue at position 78 from α-subunit significantly increases receptor binding affinity of human FSH.…”
Section: Biased Signaling At the Fshrmentioning
confidence: 99%